Farg, Fragile Lives - Violence, Power, And Solidarity In Eighteenth-Century Paris - Lindsay, Robert (Teaching History: A Journal of Methods, 1994)
As Director of Research in Modern History at the Centre National de la Recherche Scientifique in Paris and already the author of three other books on various aspects of Early Modern French social history, Arlette Farge offers a study of eighteenth-century Parisian behavioral patterns. As the author reminds the reader frequently, her monograph is not based on memoirs, chronicles, treatises, or novels, but exclusively on the judicial archives of the eighteenth century.